Dual‐Targeting Photosensitizer‐Peptide Amphiphile Conjugate for Enzyme‐Triggered Drug Delivery and Synergistic Chemo‐Photodynamic Tumor Therapy - Cheng, Yin‐Jia; Qin, Si‐Yong; Liu, Wen‐Long; Ma, Yi‐Han; Chen, Xiao‐Sui; Zhang, Ai‐Qing; Zhang, Xian‐Zheng (Advanced materials interfaces, 2020)
Chemo‐photodynamic therapy is an attractive strategy in tumor treatment. However, the combination of chemotherapeutic drug and photosensitizer in nanocarriers always elevates the risk of composition uncertainty. Here, a dual‐targeting photosensitizer‐peptide amphiphile conjugate (PpIX‐GGGK(TPP)GG‐GFLG‐R7‐RGD or pPAC) is designed to encapsulate doxorubicin (DOX) for enhanced chemo‐photodynamic tumor therapy. The amphiphilic nature of pPAC leads to the formation of core‐shell structured nanomicelles in aqueous media, where DOX is loaded in the inner core. The DOX@pPAC nanomicelle displays efficient tumor cellular uptake via integrin receptor‐mediated endocytosis using RGD peptide. After successful cell internalization with the aid of R8 peptide, DOX@pPAC exhibits rapid release of DOX and protoporphyrin IX‐peptide conjugate (PpIX‐peptide) due to the Cathepsin B‐triggered hydrolysis of GFLG linker. Simultaneously, triphenylphosphonium TPP cation will accumulate photosensitizer PpIX in subcellular mitochondria, followed by in situ generation of phototoxic reactive oxygen species (ROS) under light irradiation. In vitro investigations demonstrate that the synergistic chemotherapy and photodynamic therapy (PDT) of fabricated nanomicelles can significantly maximize the therapeutic effect against tumor cells with the minimal off‐target cytotoxicity. This work may provide an all‐in‐one nanosystem toward enhanced chemo‐photodynamic tumor therapy. The designed nanosystem (DOX@pPAC) based on covalent conjugation of photosensitizer PpIX and physical embedding of DOX, displays dual‐targeting property and synergistic chemo‐photodynamic therapy of tumor.